Análisis de la aplicación del dolo eventual en el juzgamiento de delitos de tránsito en la legislación ecuatoriana. - Coronel, Leodan E. (2022)
This research has as its essence, within a study related to the field of criminal dogmatics, to identify doctrinal bases of the relative subjective imputation of eventual fraud in its theories to establish its interpretation, comparatively analyzing the national regulations and those of the Andean countries Bolivia, Colombia and Peru and, the application of possible intent in certain cases in criminal proceedings to define its legal scope and its application in traffic accidents; with the general objective of analyzing the application of eventual fraud in the judgment of traffic crimes in Ecuadorian legislation, to specify the penalty that will be imposed by the judge in the crimes of manslaughter in traffic accidents caused by a driver in a drunken state. . For which a rigorous methodology was followed in this descriptive-theoretical research, with a mixed approach and dogmatic-legal, inductive and deductive methods, because precise conclusions were drawn based on the premise or series of propositions based on the interpretation systemic of eventual fraud in the Comprehensive Criminal Organic Code for a subsumption of facts to the criminal type in order to guarantee the adequate imputation of crimes according to the action, in a more adequate and fair manner, without violating constitutional rights and guarantees in judicial resolutions that the authority pronounces. In the legal system of Ecuador there is no rule that refers directly to possible intent, which had its origin from criminal policy. The eventual fraud arises from the need to judge the facts produced by traffic accidents, taking into consideration that it is generated when the subject does not want the typical result; but he accepts it, consents to it, or bears it.